2000
DOI: 10.1099/0022-1317-81-4-1155
|View full text |Cite
|
Sign up to set email alerts
|

Screening Congo Red and its analogues for their ability to prevent the formation of PrP-res in scrapie-infected cells

Abstract: Transmissible spongiform encephalopathies (TSEs) are incurable, fatal diseases. The dye Congo Red (CR) can cure cells infected with agents of the sheep TSE, scrapie, but is not used as a therapeutic or prophylactic agent in vivo, as its effects are small, possibly due to low blood-brain barrier permeability, and complicated by its intrinsic carcinogenicity. In this paper, the development is described of a structure-activity profile for CR by testing a series of analogues of this dye for their ability to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 55 publications
(64 reference statements)
3
94
1
Order By: Relevance
“…Targeting amyloid fibrils was also explored using amyloid dyes (Adjou et al, 1999;Beringue et al, 2000), but in vivo effects were disappointing because of their low ability to cross the blood-brain barrier. Other studies showed that targeting fibrils could result in an unexpected increase in infectivity (Beringue et al, 2000;Rudyk et al, 2000), which was also observed using the protein misfolding cyclic am-plification (PMCA) technique, when large amyloid aggregates were broken up into smaller ones (Saborio et al, 2001;Wang et al, 2010). Altogether, these works led to the emerging concept that amyloid fibrils, rather than being a pathological entity, might be the result of a protective process to sequester more dangerous soluble oligomers (Caughey and Lansbury, 2003;Silveira et al, 2005;Simoneau et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Targeting amyloid fibrils was also explored using amyloid dyes (Adjou et al, 1999;Beringue et al, 2000), but in vivo effects were disappointing because of their low ability to cross the blood-brain barrier. Other studies showed that targeting fibrils could result in an unexpected increase in infectivity (Beringue et al, 2000;Rudyk et al, 2000), which was also observed using the protein misfolding cyclic am-plification (PMCA) technique, when large amyloid aggregates were broken up into smaller ones (Saborio et al, 2001;Wang et al, 2010). Altogether, these works led to the emerging concept that amyloid fibrils, rather than being a pathological entity, might be the result of a protective process to sequester more dangerous soluble oligomers (Caughey and Lansbury, 2003;Silveira et al, 2005;Simoneau et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, ⌬V* growth in the presence of CR is about half that in the absence of CR, suggesting that the CR⅐SMA complex must undergo a smaller conformational change to reach N* than that for SMA alone. The effects of CR on both protein structure and assembly call into questions the proposed therapeutic uses of this compound or its analogs as inhibitors of amyloid fibril formation (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The ITC data obtained for A and A [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Table 2. Due to the highly hydrophobic nature of A , preparation of a purely aqueous solution was not possible.…”
Section: Itc Investigationmentioning
confidence: 99%
“…In this regard, Congo Red (CR) has been identified as a key inhibitor which reduce the neurotoxicity of AD by binding to protofibrils [11], and this inhibitory activity of CR and its derivatives have been screened as potential therapeutics against amyloid fibril formation [17][18][19][20]. The apolar moiety of CR is comprised of a biphenyl group at the center of the molecule and is extended by a diazo and two naphthalene groups.…”
Section: Introductionmentioning
confidence: 99%